Pengaruh Pencahayan Buatan terhadap Kenyamanan Visual Pengunjung pada Interior Boutique Banana Republic di Surabaya - Jocelyn Hadianto; Sumartono Sumartono; Poppy Firtatwentyna Nilasari (Intra, 2013)
Lighting is one of the important factors in interior design. The role of lighting does not only provide light, but also accentuates the aesthetic and the atmosphere of a room. It can also affect the image of the interior space. The purpose of this research is to analyze and find an optimal lighting design as a solution by using Banana Republic Boutique in Surabaya as the case.The methods used are qualitative and quantitative. The first step was observing and measuring the data in the field, using a Luxmeter to recognize the illumination rate of the room. The second step was  distributing questioners and doing an interview to know the visual comfort. The third step was doing a simulation with DIALux v.4.7 program. Finally, the result will be verified with the literature.The research shows that the field measurement using Luxmeter and simulation with DIALux v.4.7 fulfills the SNI requirement. Yet, the boutique still need to put the light distribution placement to a consideration as it is not well distributed, so that it will increase the aesthetic quality of the lighting in the store and will also increase the level of comfort for the visitors.